MAGNETIC RESONANCE IMAGING IN THE STAGING OF MALIGNANT LYMPHOMAS - A. I. Mikhaylov; I. E. Tyurin; V. O. Panov (Вестник рентгенологии и радиологии)
Computed tomography, 18FDG-PET and the hybrid FDGPET/CT are the most commonly used diagnostic tools for the initial staging and treatment response assessment of malignant lymphomas. MRI techniques such as whole-body MRI and diffusionweighted imaging may become good radiation-free alternatives to FDG-PET/CT. Diffusion-weighted imaging is characterized by high sensitivity for the detection of lesions and allows quantitative assessment of diffusion that may aid in the evaluation of malignant lymphomas. This article will review the value of these emerging MRI techniques for the staging and response assessment of malignant lymphoma.